Analisis pembelajaran daring pada materi dinamika partikel ditinjau dari komunikasi matematis - Titin Supriyatin; Dwi Aprillia Setia Asih; Avini Nurazhimah Arfa (Navigation Physics : Journal of Physics Education, 2021)
This study aims to analyze the achievement of each indicator that measures students' mathematical understanding abilities in basic physics courses on particle dynamics material. This research is a qualitative descriptive study that seeks to describe the analysis of students' mathematical understanding abilities. The research subjects were 6 class 3 semester students of biology education consisting of 198 students. The data collection method used includes tests of students' mathematical understanding abilities in basic physics courses which include particle dynamics material. Based on the results of the study, it was concluded that the level of ability of biology education students in basic physics courses was as follows: (1) Students already had the ability to solve problems was good enough on particle dynamics material from questions 1 to 5 had an average percentage of 56.2% , (2) Students have reasoning abilities (reasoning on particle dynamics material from questions 1 to 5 have an average percentage of 14.4%, (3) Students have communication skills (communication) on particle dynamics material from questions 1 to 5 have The average percentage is 12.2%, (4) students have the ability to make connections to the dynamic material of particles from questions 1 to 5, have an average percentage of 12.4%; (5) students have representation ability ) on the particle dynamics material from questions 1 to 5 has an average percentage of 4.8%.